Jenis-Jenis Foraminifera Bentik di Teluk Bayur Padang, Sumatra Barat - Radilla Silmiah; - Jabang; Siti Salmah (Jurnal Biologi Universitas Andalas, 2013)
A study on benthic Foraminifera in Padang, West Sumatra was conducted from June 2012 to January 2013. The main purpose of this study was to determine the types spesies of benthic foraminifera at Teluk Bayur, Padang, West Sumatra. Samples of foraminifera were collected purposively at Teluk Bayur. A total of six spesies of foraminifera (Quinqueloculina lamarckiana, Triloculina fichteliana, Miliolina subrotunda, Spiroloculina communis, Operculina ammonoides and Operculina complanata) was collected that belong to 2 Suborder (Miliolina and Rotaliina), 3 family (Hauerinidae, Spiroloculinidae, and Nummulitidae), and 5 genera. The highest number of individuals was from suborder Rotaliina (Operculina complanata 64.597 individuals).Keywords : Foraminifera, Benthic, Teluk Bayur